(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The aim of the research is to identify the reality of the organizational climate of private kindergarten directors in Damascus Governorate, from the point of view of private kindergarten administrators as individuals of the research sample, in addition to identifying the differences between the degrees of the responses of the sample members according to the research variables (scientific qualification and years of experience), and the research was based on the descriptive analytical method. A questionnaire consisting of (47) items was used, and it was distributed to a random sample that included (50) directors from private kindergartens in Damascus governorate, or 42% of the original community, whose number is (119) managers, and the results of the research showed that the reality of The organizational climate of the directors was high, in addition to the absence of statistically significant differences between the averages of the responses of the members of the research sample on the total score of the questionnaire attributable to the variables of academic qualification and years of experience.